CONCEPT MAPPING TO IMPROVE THE READING ABILITY OF THE SECOND SEMESTER STUDENTS OF ENGLISH DEPARTMENT - CANDRA JAYA (Premise: Journal of English Education and Applied Linguistics, 2012)
ABSTRACT: The objective of the study was to develop the concept mapping strategy to improve the students’ reading ability at the second semester university students . The researcher employed classroom action research which was conducted within two Cycles in which each Cycle comprised planning, implementing, observing, and reflecting. Four instruments consisting of observation sheet, field notes, interview, and test were used to collect the data in Cycle 1. Five instruments consisting of observation sheet, field notes, interview, test, and questionnaire were used to collect the data in Cycle 2.The findings of the students’ academic atmosphere from observation and field note described the students’ learning interaction. Interview in Cycle I and 2 revealed the students felt comfortable, happy, and enjoyed learning reading using concept mapping because concept mapping was helpful. Questionnaire indicated 47% of the students’ responses were “strongly agree” and 53% of their responses were “agree” for the benefit of concept mapping implementation. The finding of the students’ reading achievement showed that out of 25 students, 19 students got the scores above 60 in Cycle 1; meanwhile, all students got the scores above 60 in Cycle 2.